Crowdfunding Market in the UAE: Triangulation Study for the Success Factors in the Market - EFRAIJ, DALIA AHID (2022)
Crowdfunding is considered a new funding type in the UAE financial industry. It started to gain the attention as an emerging market that holds capitalization opportunities for SMEs and start-ups. Research has shown that crowdfunding is expected to grow in size in the developing countries. However, the related studies to the crowdfunding market in the UAE were almost not found, therefore, this study aims to investigate the crowdfunding market by examining the extent of certain success factors, namely awareness, knowledge, trust, and regulations in United Arab Emirates. The study methodology was based on the triangulation mixed method in which quantitative data was obtained through an online survey, professional opinions are extended by conducting interviews, and finally a comparative analysis was significant to evaluate the market position compared to a well-developed model from the UK crowdfunding market. The associated quantitative and qualitative data analysis revealed that crowdfunding market in the UAE has founded a good level of regulations for such market. However, the level of awareness, knowledge, and trust remains subject of enhancement and improvement. Those results may infer that there is a possible promising future for crowdfunding in the UAE if the rest of success factors were attained. In addition, the paper advises all market participants, including the government, platforms, project owners, and educational institutions, to take particular steps to contribute to the market's growth. Nevertheless, the study still holds certain limitations related to the methodology that need to be likely improved by further future studies.